Colegios profesionales, relaciones colegiales y potestad sancionadora - Sanz Rubiales, Iñigo (2019)
Regardless of doctrinal discussions about Peruvian ordainment, it is undoubtedly deducedthat Professional Schools and public Administrations.The juridical relationship between collegiate and School is regarded, in Spanish jurisprudence,as “special subjection relationship”, typically “domestic”, category usedtraditionally to justify limitation of rights; however, the Peruvian constitutional Courtdoes not assume this doctrine. This work demonstrates that the licit flexibility of theprinciple of legality derives from the corporate-representative constitution of schools.Consequently, collegiate sanctions cannot be identified with disciplinary sanctions ofthe personnel. After certain doubts, the Constitutional court states with good criteriathe compatibility of both, derived from the diversity of juridical goods protected.